TECHNOLOGY OF INFORMATION COMPETENCE FORMATION BASED ON THE PREVENTION OF VIRTUAL ADDICTION IN STUDENTS (American Journal of Pedagogical and Educational Research, 2023)
The article deals with the need to protect primary school pupils against the threat of harmful information, the negative effects of the information threat, and the pedagogical conditions for prevention.